Posisi Ulama dalam Pemilihan Gubenur Jawa Timur Perspektif Fiqh Siyasah - Roikhatul Hamidah (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2019)
This paper aims to find out the Ulama's standpoint in the practice of Election of Governors from fiqh siyasah perspective. The results of the study concluded that the election of governor in East Java conducted through direct election by the people. The influence of Ulama in the election of governors and deputy governors of East Java to the people drawn the interest of politicians. It is because the Ulama have the legality, influence, and social capital that are the parameters that can influence the tide of votes in the election of the Governor of East Java that is still heavily associated with Pesantren culture. In Islam, there is no prohibition for Ulama to take part in political life as the Prophet besides being the bearer of the treatise of Allah also become as umara'. At the time of khulafaur Rasidin almost every line of sUlama held the government position. The most important thing is to be able to control the umara/government in carrying out its duties as the people's representative. This kind of indicator will elevate the image of the Ulama as a servant of God among other creatures.